The state-of-the-art in expert recommendation systems. (June 2019) - Nikzad–Khasmakhi, N.; Balafar, M.A.; Reza Feizi–Derakhshi, M.
Abstract: The recent rapid growth of the Internet content has led to building recommendation systems that guide users to their needs through an information retrieving process. An expert recommendation system is an emerging area that attempts to detect the most knowledgeable people in some specific topics. This detection is based on both the extracted information from peoples' activities and the content of the documents concerned with them. Moreover, an expert recommendation system takes a user topic or query and then provides a list of people sorted by the degree of their relevant expertise with the given topic or query. These systems can be modeled by information retrieval approaches, along with search engines or a combination of natural language processing systems. The following study provides a critical overview of existing expert recommendation systems and their advantages and disadvantages, considering as well different techniques employed by them.